The Effectiveness of Blended Learning in Improving Midwifery Students' Skills - Fathiyati Fathiyati; Didi Sutisna; Ewin Suciana; Siti Madinah Ladjamuddin (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2024)
The development of digital technology has driven changes in the learning system in midwifery education, one of which is through the implementation of blended learning. This learning model combines face-to-face and online learning to improve the effectiveness of students' learning processes. This study aims to explore the effectiveness of blended learning in improving the skills of midwifery students. The study used a qualitative approach with a descriptive phenomenological design. The study participants were 15 midwifery students selected using a purposive sampling technique. Data collection was conducted through in-depth interviews, observation, and documentation. Data analysis used thematic analysis through the processes of data reduction, coding, theme identification, and interpretation of meaning. The results showed that blended learning had a positive impact on the learning process of midwifery students. Students experienced flexibility in accessing learning materials, improved understanding of theory and clinical skills, and increased motivation and independence in learning. The use of learning videos, virtual simulations, and online discussions helped students better prepare for laboratory and clinical practice. In addition, blended learning also increased learning interactivity and student participation in academic discussions. However, the implementation of blended learning still faces several obstacles, such as limited internet connection, online learning fatigue, and limitations in direct clinical practice. This study concludes that blended learning is an effective and adaptive learning method for improving midwifery students' skills in the digital era when supported by optimal technological infrastructure and learning design